Change And The Role Of Intimidation Mechanisms - Iorgulescu, Gabriela (Advances in Social Sciences Research Journal, 2017)
Change in an organization is not a coherent, compact process – depending on situations, psychosocial backgrounds, perception of the process by different groups of individual, but can have an asynchronous course, sometimes conflicting, with breakdowns which can have unexpected side effects, such as blocking initiatives, distortion of the correct perception of events, action paralysis, etc. Tensions and insecurities may give rise to different maladaptive behaviors. In the following are highlighted certain characteristics of the reactions of leaders in the organizational systems to the actions of some subordinated reformers as a series of intimidation rituals. Each successive “control ritual” represents an escalation of the authority’s efforts to discourage an individual (and those who might support) to continue on promoting the reform.